2001
DOI: 10.1136/jnnp.70.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Pentagon copying is more impaired in dementia with Lewy bodies than in Alzheimer's disease

Abstract: Objectives-In many cases the clinical diVerentiation of patients with dementia with Lewy bodies (DLB) from those with Alzheimer's disease (AD) has been diYcult. Because many neuropsychological studies have reported greater visuospatial/ constructional impairment in DLB than in AD, it was determined whether accuracy in copying the interlocking pentagons item on the mini mental state examination (MMSE) may be helpful in distinguishing patients with DLB from those with AD relatively early in the course of the dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 27 publications
8
86
2
4
Order By: Relevance
“…Likely because of its complexity, copy of the ROCF has not been extensively used in LBD, whereas some interesting observations came from the copy of the intersecting pentagons included in the MMSE. Ala et al [164] found that patients with LBD were more likely than those with AD to copy pentagons incorrectly, and suggested that this impairment might help identifying LBD patients. Cormack et al [165] confirmed that LBD patients show significantly lower performance in copying pentagons with respect to AD; moreover, while in AD the impairment in copying figures was correlated with general cognitive deterioration, in LBD drawing was correlated with visuospatial tasks only, thus suggesting the existence of a specific defect in this disease.…”
Section: Drawing Disorders In Lewy Body Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Likely because of its complexity, copy of the ROCF has not been extensively used in LBD, whereas some interesting observations came from the copy of the intersecting pentagons included in the MMSE. Ala et al [164] found that patients with LBD were more likely than those with AD to copy pentagons incorrectly, and suggested that this impairment might help identifying LBD patients. Cormack et al [165] confirmed that LBD patients show significantly lower performance in copying pentagons with respect to AD; moreover, while in AD the impairment in copying figures was correlated with general cognitive deterioration, in LBD drawing was correlated with visuospatial tasks only, thus suggesting the existence of a specific defect in this disease.…”
Section: Drawing Disorders In Lewy Body Dementiamentioning
confidence: 99%
“…No 2-year decline in FTD Comparison AD-LBD Nervi [152] Figure copying LBD worse than AD Crowell [153] Figure copying LBD worse than AD Tiraboschi [154] Figure copying LBD worse than AD; no differences in pentagon copying Cahn-Wiener [156] CDT No differences in overall score, but more conceptual and planning errors in LBD Hamilton [157] Clock copying No differences, but lower scores predicted steeper decline in LBD Cagnin [158] CDT LBD worse than AD Palmqvist [159] CDT, cube copying LBD worse than AD Gnanalingham [162] CDT, clock copying No difference in CDT; LBD worse than AD in clock copying Ala [164] Pentagon copying LBD worse than AD Cormack [165] Pentagon copying LBD worse than AD Connor [166] Pentagon copying No difference Caffarra [167] Figure copying, No difference in figure copying, pentagon copying worse scores in LBD on an analytic scoring system for pentagon copying AD, Alzheimer's disease; VaD, vascular dementia; sVaD, subcortical VaD; FTD, frontotemporal dementia; bvFTD, behavioral variant of FTD; PA, progressive aphasia; LBD, Lewy body dementia; CDT, Clock drawing test; ROCF, copy of Rey's complex figure. Reference numbering follows the text.…”
Section: Drawing Disorders In Vascular Dementiamentioning
confidence: 99%
“…17 Executive function was determined using the modified ("one touch stockings") version of the Tower of London task from the CANTAB battery, phonemic fluency (words beginning with "F" in 1 minute), 18 and semantic fluency (animals in 90 seconds). 19 The pentagon copying item of the MMSE was graded using a modified 0 to 2 rating scale, 20 as a measure of visuospatial function. Language domain was assessed using the naming (0-3) and sentence (0-2) subsets of the MoCA test.…”
Section: Participants Between June 2009 and Decembermentioning
confidence: 99%
“…A recent metaanalytic study by Collerton et al (2003) systematically reviewed 21 studies comparing the cognitive performance of DLB patients; they found that the effect size (Cohen's d: averaged across multiple cognitive domains) was, in fact, larger for DLB (2.0-2.2) than AD (1.4-1.6) patients. Studies comparing AD and DLB patients have pinpointed some differences in cognitive performance: memory impairment is less severe in DLB than AD (e.g., Calderon et al, 2001;Salmon et al, 1996;Shimomura et al, 1998), while visual-perceptual and spatial abilities are more impaired (e.g., Ala et al, 2001;Calderon et al, 2001;Gnanalingham et al, 1997;Salmon et al, 1996). Consistent with the neuropsychological profile, functional imaging studies show that patients with DLB more commonly have reduced perfusion in the occipital lobes than AD patients (Ishii et al, 1999;Lobotesis et al, 2001).…”
Section: Introductionmentioning
confidence: 51%